Ammiralius, Mirdalim, Amirdalis - kreacja muzułmańskich dowódców w czasie walk o Antiochię w łacińskich źródłach doby pierwszych krucjat (do około połowy XII wieku) = Ammiralius, Mirdalim, Amirdalis - the depiction of muslim commanders during the struggle of Antioch in Latin sources from the first crusade (until c. the mid-twelfth century) - Pełech, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article considers three main issues: the representation of the secondary Muslim commanders in descriptions of the military struggles under the city of Antioch; the transmission of content in sources from the next generations of the First Crusade`s historians; the attempt to identify the Muslim commanders mentioned in Latin sources with real historical figures.
Keywords: wyprawy krzyżowe; pierwsza wyprawa krzyżowa; oblężenie Antiochii; przedstawienie "obcego"; muzułmanie; transmisja treści; kronikarze pierwszej krucjaty; the First Crusade; Siege of Antioch; representation of the "other"; the Muslims; the content`s transmission; the First Crusade`s chroniclers